Anxiety and depression in patients who receive anti‐VEGF treatment and the usability and feasibility of e‐mental health support: the E‐PsEYE pilot study. (29th May 2021) - van der Aa, Hilde PA; van Rens, Ger HMB; Verbraak, Frank D; Bosscha, Machteld; Comijs, Hannie C; van Nispen, Ruth MA
Abstract: Purpose: E‐PsEYE is an internet‐based, guided self‐help course, following the principles of cognitive behavioural therapy, to reduce anxiety and depression in patients with retinal exudative diseases who receive anti‐vascular endothelial growth factor (anti‐VEGF) treatment. The purpose of this study was to determine the prevalence and related factors of anxiety and depression in this population and evaluate the usability and feasibility of E‐PsEYE. Methods: Symptoms of anxiety and depression and related factors were determined in 90 patients (mean age 77 years, 58% female), based on multiple logistic regression analysis. Five patients with mild to moderate depression/anxiety tested the usability of E‐PsEYE. They were asked to think aloud while completing two modules of the intervention and freely explore system features. The feasibility of the total E‐PsEYE intervention was tested in 14 patients with mild to moderate depression/anxiety, based on a single arm pre‐post study with a follow‐up of three months: fidelity, acceptability, feasibility of study methods and potential effectiveness were explored. Results: Fifty‐three percent of the total study population experienced at least mild anxiety and/or depression symptoms. Especially female patients (odds ratio (OR) 3.89, 95% confidence interval (CI) 1.33–11.40), those who experienced limitations in daily life activities due to vision loss (OR 9.67; 95% CI 3.18–29.45) and those who experienced loneliness (OR 3.53, 95% CI 1.14–10.95) were more likely to have anxiety/depression. The usability study raised several possibilities for improvement, based on which E‐PsEYE was improved. The feasibility study showed adequate fidelity and acceptability. Most participants were satisfied with the results (79%). There was a high response rate, no loss to follow‐up and mental health problems decreased in more than half of the patients. The Wilcoxon signed rank test indicated lower post‐test ranks compared to pre‐test ranks (depression Z −1.34, p  = 0.18; anxiety Z −1.45, p  = 0.15). Conclusions: Mental health problems are prevalent in patients who receive anti‐VEGF treatment. Healthcare providers should recognise these problems and related factors in order to refer patients to appropriate care in a timely manner. Outcomes on the usability and feasibility of E‐PsEYE are promising as a prelude to performing a randomised controlled trial, which will shed more light on its (cost‐)effectiveness.